Foramen Magnum: A Morphometric Study in Dried Human Skulls - Gupta, Anil Kumar; Shah, Gaurav Jung; Chaudhary, Archana; Prasad, Ram Jiban (Nepal Journal of Health Sciences, 2022)
Introduction: The foramen magnum is the largest foramen or opening present in the base of the skull. The dimensions of the foramen magnum are clinically crucial because many vital structures are passing through it.Objective: The aim of the study was to determine the different shapes of the foramen magnum and its anteroposterior diameter and transverse diameter.Methods: This study was conducted on 32 dry human skulls of unknown age and sex. All the important parameters were studied using a vernier caliper.Results: The mean transverse diameter (TD) was found to be 27.75 ± 2.47mm (Mean ± SD) and the mean anteroposterior diameter (APD) was found to be 34.62 ± 3.58mm (Mean ± SD). The various shapes of the foramen magnum were observed. The most common shape was oval 46.9%, followed by round18.8%, tetragonal 15.6%, hexagonal 12.5%, and irregular 6.3%.Conclusions: In our study, the most common shape of the foramen magnum was oval; this can help the surgeons to perform post-cranial surgery and surgery near the foramen magnum as an oval shape indicates the narrow operative field. The study may also be helpful for anatomists for study purposes and forensic experts to determine the identity of different populations when compared to other studies.